Bibliometric Analysis Of Research Trends About Opinion On Government Financial Statements By Financial Examination Board Of The Republic Of Indonesia - Em Zaki Umarak; Desiana Rachmawati; Macelina Shally Ardias; Abdi Azizul Hakim (International Journal of Economics, Business and Innovation Research, 2024)
Research that discusses opinion of the Auditing Body Finance The Republic of Indonesia is widespread done since 2006 and continuing increase until moment This. Mapping about theme This need done For know trend in 20 years final. Objective did it study This is For identify themes necessary research studied more Far so that truly own novelty and benefits for study furthermore. Study This use approach studies literature with approach quantitative through analysis statistics so called descriptive with analysis bibliometrics. At least 996 articles were collected through the next Publish and Perris (PoP) application processed through application VoSViewer For analyzed. Research result prove lower with using the keyword "BPK Audit Opinion" is known that focus on studies This more to agency executor of the audit, namely the Audit Agency Finance. Temporary variables other Still not enough Lots studied and needed study more carry on. Discussion theme around BPK audit opinion reached peak For become center study in 2017 and tends to decline that proves that interest researcher For theme this is also starting decrease . Whereas Still Lots things that can dug about matter This especially those linked with competence examiner/auditor, conditions agency external (auditee or government area), and so on.